Dietary Thioproline Decreases Spontaneous Food Intake and Increases Survival and Neurological Function in Mice - Navarro, Ana (2007)
Male mice on a diet supplemented with thioproline (l-thiazolidine-4-carboxylic acid), a physiological metabolite of 5-hydroxytryptamine, at 2.0 g/kg of food from 28 weeks of age and for their entire life, showed a 23-29% increased median and maximal life span. These survival increases were associated with improved neurological functions. Compared to control mice, thioproline-supplemented mice had a 20% lower integral spontaneous food intake, and 10% lower body weight at 100 weeks of age. Body weight showed a statistically significant inverse relationship with survival and neurological performances. Thioproline-supplemented mice exhibited a 58-70% decrease of the age-dependent oxidative damage in brain and liver mitochondria at 52 weeks (old mice) and 78 weeks (senescent mice) of age, respectively. The age-associated decrease of brain mitochondrial enzyme activities, NADH-dehydrogenase, cytochrome c oxidase, and mitochondrial nitric oxide synthase (mtNOS), in old and senescent mice were markedly prevented (51-74%) by thioproline. In vitro, thioproline neither exhibited direct antioxidant activity nor had any effect on the electron transfer or mtNOS functional activities of brain and liver mitochondria. It is surmised that thioproline induces an anorexic effect associated with improved survival and neurological function through a decreased oxidative damage and regulation that may involve hypothalamic appetite centers.